Transaction Costs, Market Failures and Economic Development - TODOROVA, Tamara (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
This paper relates economic development to transaction costs. It reveals the triad transaction costs-market failure-economic underdevelopment. Many scholars attribute the problems of development to the failure of markets to perform their role of resource allocation. Some deny market failure and blame government instead. Of those who trace the roots of economic backwardness to market failure, few, if none, investigate transaction costs in their linkage with market failure. This paper tries to bridge development economics with transaction cost theory and new institutional analysis.